Pengaruh Beberapa Formulasi Sitokinin Terhadap Penyediaan Bibit dan Pertumbuhan Eksplan Tanaman Pule Pandak (Rauvolfia serpentina (L.) Benth. ex Kurz) Secara In Vitro - Anita Widya Karyaningtyas; Ani Lestari; Edhi Sandra (JURNAL AGROPLASMA, 2023)
Propagation of pule pandak (Rauvolfia serpentina (L.) Benth. Ex Kurz) conventionally shows growth from seeds and stem cuttings of less than 15%. The low growth percentage is due to the seeds have hard coats, so the germination of the seeds is very low. One of the technologies that can be used and provides hope in the supply of seeds in large quantities and in a relatively short time is the in vitro culture technique. The aim of this study was to determine does the several cytokinin formulations administration affected the growth of pule pandak (Rauvolfia serpentina (L.) Benth. ex Kurz) plant explants. The study was conducted at Esha Flora, Bogor from April 2022 to July 2022. The experiment used a single factor Completely Randomized Design (CRD) consisting of 1 factor using 4 combinations of cytokinins (2-IP, TDZ, BAP and Kinetin) and repeated 10 times so that there are 40 experimental units for 12 weeks. The data obtained were then analyzed using the ANOVA test at a significant level of 5%. The results showed that the S1 treatment (Modified MS Media + 2-IP 2 mg/l + TDZ 0.1 mg/l + BAP 0.5 mg/l and Kinetin 0.5 mg/l) was the best cytokinin formulation to produce the highest average number of shoots was 8.87 shoots, the highest explant height was 2.49 cm and the fastest average of somatic embryogenesis emergence time was 23.3 DAP. Somatic embryo phase in treatment S1, S2 and S3 experienced globular, heart and torpedo phases. Keywords: Cytokinine, Somatic Embryogenesis, Tissue Culture, Rauvolfia serpentina (L.) Benth. Ex Kurz